2016
DOI: 10.1371/journal.pone.0167708
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Cataract Surgery in Urban and Rural Population in the South Indian State of Andhra Pradesh: Rapid Assessment of Visual Impairment (RAVI) Project

Abstract: ObjectiveTo assess the visual outcomes after cataract surgery among urban and rural population aged ≥40 years in the South India state of Andhra Pradesh.MethodsA population based cross-sectional study was conducted in which 7800 subjects were sampled from two rural and one urban location. Visual Acuity was assessed and eye examination were performed by trained personnel. A questionnaire was used to collect personal and demographic information, and history of cataract surgery. Blindness and moderate Visual Impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Visual outcomes after cataract surgery were better than in many other LMIC (Table 5) [19][20][21][22][23][24][25][34][35][36][37][38][39], with poor outcomes only slightly higher than the WHO recommended levels of <5% (12.1% presenting VA; 8.8% best correction VA). Visual outcomes have improved significantly in Sri Lanka due to the near universal use of IOLs, which have recently been provided free by the Ministry of Health.…”
Section: Discussionmentioning
confidence: 87%
“…Visual outcomes after cataract surgery were better than in many other LMIC (Table 5) [19][20][21][22][23][24][25][34][35][36][37][38][39], with poor outcomes only slightly higher than the WHO recommended levels of <5% (12.1% presenting VA; 8.8% best correction VA). Visual outcomes have improved significantly in Sri Lanka due to the near universal use of IOLs, which have recently been provided free by the Ministry of Health.…”
Section: Discussionmentioning
confidence: 87%
“…A large proportion of those who had bilateral cataract surgery had URE suggesting the need for follow‐up care after cataract for the correction of refractive error. There are not many studies that reported on the burden of URE after cataract surgery in the elderly in residential care in India though the studies have reported on visual outcomes after cataract surgery in the community‐dwelling populations 32‐34 . URE was reported as the leading cause of visual impairment after cataract surgery in these studies ranging from 28.7% to 38.8%.…”
Section: Discussionmentioning
confidence: 99%
“…A recent large population based study amongst adults in southern India reiterated that correction of refractive errors is required to provide good visual recovery and achieve the benefit of cataract surgery. 32 Most of these free-surgeries in rural areas are done through outreach programs as part of the National Program for Control of Blindness (NPCB) activity where they are transported to the base hospital for surgeries and a few given one-time free spectacles six weeks after cataract surgery. Though it is mandatory to prescribe and provide spectacles free of cost to post-surgery to poor patients, we found that just about a quarter of patients were prescribed and provided spectacles.…”
Section: Discussionmentioning
confidence: 99%